Development and Evaluation of the Utilization of Augmented Reality to Enhance the Physics Teaching and Learning Process Using the Design Science Research Method - Mahmud, Nurul Huda; Inan, Dedi Iskandar; Yusuf, Irfan (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Quality education relies on effective learning methods. However, some students struggle to grasp the concepts taught in basic physics courses, often due to the lack of innovative teaching approaches in physics education. Traditional teaching methods can lead to student disinterest and difficulty in understanding the material. To address these challenges, integrating engaging technology into education is essential. Augmented Reality (AR) technology, which blends virtual elements with the real world, has emerged as a popular learning tool. But can AR effectively enhance learning experiences at FKIP UNIPA? To explore this, research was conducted to develop AR teaching materials using the Design Science Research method and gauge student interest in AR. Hypothesis testing using the Hedonic Motivation System Adoption Model (HMSAM) revealed that students at FKIP UNIPA responded positively to the AR teaching materials. The results showed that factors like perceived usefulness, curiosity, and enjoyment significantly influence students' willingness to use AR by 53.5%. In summary, the findings suggest that AR technology holds promise in improving learning outcomes and student engagement in physics education.